Mitochondrial cysteine synthase complex regulates O-acetylserine biosynthesis in plants. - Wirtz, M; Beard, K; Lee, C; Boltz, A; Schwarzländer, M; Fuchs, C; Meyer, A; Heeg, C; Sweetlove, L; Ratcliffe, R; Hell, R (2012)
Cysteine synthesis is catalyzed by serine acetyltransferase (SAT) and O-acetylserine (thiol) lyase (OAS-TL) in the cytosol, plastids, and mitochondria of plants. Biochemical analyses of recombinant plant SAT and OAS-TL indicate that the reversible association of the proteins in the cysteine synthase complex (CSC) controls cellular sulfur homeostasis. However, the relevance of CSC formation in each compartment for flux control of cysteine synthesis remains controversial. Here, we demonstrate the interaction between mitochondrial SAT3 and OAS-TL C in planta by FRET and establish the role of the mitochondrial CSC in the regulation of cysteine synthesis. NMR spectroscopy of isolated mitochondria from WT, serat2;2, and oastl-C plants showed the SAT-dependent export of OAS. The presence of cysteine resulted in reduced OAS export in mitochondria of oastl-C mutants but not in WT mitochondria. This is in agreement with the stronger in vitro feedback inhibition of free SAT by cysteine compared with CSC-bound SAT and explains the high OAS export rate of WT mitochondria in the presence of cysteine. The predominant role of mitochondrial OAS synthesis was validated in planta by feeding [(3)H]serine to the WT and loss-of-function mutants for OAS-TLs in the cytosol, plastids, and mitochondria. On the basis of these results, we propose a new model in which the mitochondrial CSC acts as a sensor that regulates the level of SAT activity in response to sulfur supply and cysteine demand.